Regional Electromyography of the Infraspinatus and Supraspinatus Muscles During Standing Isometric External Rotation Exercises. (September 2022) - Whittaker, Rachel L.; Alenabi, Talia; Kim, Soo Y.; Dickerson, Clark R.
Background: Whole-muscle electromyography (EMG) data of the rotator cuff support external rotation (ER) strengthening exercises during shoulder rehabilitation. However, distinct neuroanatomic regions in the supraspinatus and infraspinatus exist. Differences in regional muscle activity occur during rehabilitation exercises, but little information is available for ER exertions. Hypothesis: Regional infraspinatus and supraspinatus muscle activity during standing ER exertions will differ with posture and intensity. Study Design: Descriptive laboratory study. Level of Evidence: Level 5. Methods: Twenty healthy individuals (12 men, 8 women) participated. Fine wire electrodes were inserted into 2 supraspinatus and 3 infraspinatus muscle regions. EMG data were recorded during standing isometric ER exertions at 2 intensities (maximal, submaximal) and in 7 postures defined by the angle (0°, 30°, 90°) and plane (abduction, scaption, flexion) of arm elevation. EMG data were normalized to maximum voluntary isometric contraction (% MVIC) to examine the influences of posture, intensity and their interaction on muscle activity. Results: Superior infraspinatus activity was higher in 0° of elevation (50.9% ± 5.7% MVIC) versus 30° of flexion (37.4% ± 3.9% MVIC) at maximal intensity. Inferior infraspinatus activity was higher in 90° of scaption (max = 59.8% ± 2.8% MVIC, submax = 29.4% ± 1.9% MVIC) versus 0° of elevation (max = 42.3% ± 4.5% MVIC, submax = 22.4% ± 2.8% MVIC) ( P = 0.02, P = 0.05, respectively). Anterior supraspinatus activity was highest in 90° of adbuction (max = 61.6% ± 3.1% MVIC; submax = 39.1% ± 3.8% MVIC) and lowest in 30° of flexion (max = 29.0% ± 3.4% MVIC, submax = 15.6% ± 1.7% MVIC) and 90° of flexion (max = 34.6% ± 2.4% MVIC, submax = 14.8% ± 1.9% MVIC). Posterior suprasptinatus activity was lowest in 0° of elevation (34.2% ± 3.0% MVIC), 30° of flexion (33.0% ± 3.6% MVIC) and highest in 90° of abduction (56.2% ± 4.1% MVIC) and 90° of scaption (46.7% ± 2.8% MVIC) (all P s < 0.04). Conclusion: Regional infraspinatus and supraspinatus muscle activity differed with posture and intensity. Superior and middle infraspinatus muscle activities were similar across postures, but inferior infraspinatus activity was highest in 90° of arm elevation. Anterior and posterior supraspinatus activities were higher in the abduction and scaption planes, especially at 90° of elevation, as compared with the flexion plane. Clinical Relevance: In shoulder rehabilitation of supraspinatus tendon injuries, ER exercises in the flexion plane challenge the whole infraspinatus muscle and require lower supraspinatus muscle activity.